Adapting Muhammadiyah's Da'wah Strategies to Engage Generation Z in the Digital Age - Agustina, Fitri; Asrofi, Asrofi; Hakim, Nur (CV. Bimbingan Belajar Assyfa, 2024)
This study examines the adaptation of Muhammadiyah's da'wah strategies to modern technological advancements, with a focus on engaging Generation Z, who are known for their tech-savviness. The research aims to identify effective methods for delivering religious messages to this demographic through digital platforms. Utilizing a library research method, analytical data were gathered from a variety of sources, including books, academic journals, research papers, and other relevant literature. The study found that Muhammadiyah's digital da'wah model is sufficiently flexible to integrate contemporary technological tools, ensuring continuous and effective religious communication. Specific findings highlight the importance of using social media, video content, and interactive online platforms to engage Generation Z. Additionally, the research underscores the need for da'i (preachers) to be well-versed in digital communication, possess deep knowledge of religious content, and create engaging, relevant material.This adaptive approach not only addresses technological advancements but ensures that the da'wah message is impactful and resonates with Generation Z. The practical implications of this study suggest that digital da'wah can significantly enhance the reach and effectiveness of religious communication in the modern age. In conclusion, Muhammadiyah's use of digital da'wah demonstrates its capacity to evolve and remain relevant, particularly in communicating with a tech-oriented audience like Generation Z.